Spectrophotometric Determination of Copper(II) and iron(III) with 2,4-Dihydroxy-5-Bromaocetophenone Thiosemicarbazone - Desai, M.J.; Desai, K.K. (Asian Journal of Chemistry, 2010)
2,4-Dihydroxy-5-bromoacetophenone thiosemicarbazone (DHBAT) was synthesized and used as a spectrophotometric reagent for copper and iron. Cu(II) and Fe(II) form yellow colored complex at pH 6.0 and 4.0 and show maximum absorption at 420 nm and 380 nm respectively. Molar absorptivities for Cu(II)-DHBAT and Fe(III)-DHBAT are 0.145 x 104 lit/mol cm and 0.6 x 104 lit/mol cm respectively. Cu(II)-DHBAT has 1 : 1 (M : L) stoichiometry while Fe(III)-DHBAT complex has 1 : 2 (M : L) stoichiometry. Beer's law is obeyed up to 12.7 ppm of Cu(II) ion and 9.41 ppm of Fe(III) ion. The reagent has been found to give satisfactory results for the analysis of copper in brass and iron in pharmaceutical preparation. Formation of the complex has also been supported from the IR spectral data.